2005
DOI: 10.1515/jpm.2005.080
|View full text |Cite
|
Sign up to set email alerts
|

Indications and limitations for a neonatal pulse oximetry screening of critical congenital heart disease

Abstract: Our findings indicate that pulse oximetry is a non-invasive and specific screening tool for an early detection of CCVMs, and is easily applicable to a small size nursery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 12 publications
4
32
0
3
Order By: Relevance
“…20,25,28 The positive predictive value of 77.78% was comparable to that obtained by Koppel et al who obtained a PPV of 75%; however, it is higher than that obtained by other workers like Rosati et al, Richmond et al and Hoke et al but less than that obtained by Arlettaz, et al 18,19,21,25,28 The negative predictive value of 99.9% is comparable to all other studies which have reported it to be between 98% to 100%. [18][19][20][21]25,28,29 The false positive rate was to be found to be 0.08% and was comparable to that obtained by Reich, et al, who reported it to be 0.09% at >24 hour. 29 A low false positive rate reduces the number of unnecessary echocardiograms.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…20,25,28 The positive predictive value of 77.78% was comparable to that obtained by Koppel et al who obtained a PPV of 75%; however, it is higher than that obtained by other workers like Rosati et al, Richmond et al and Hoke et al but less than that obtained by Arlettaz, et al 18,19,21,25,28 The negative predictive value of 99.9% is comparable to all other studies which have reported it to be between 98% to 100%. [18][19][20][21]25,28,29 The false positive rate was to be found to be 0.08% and was comparable to that obtained by Reich, et al, who reported it to be 0.09% at >24 hour. 29 A low false positive rate reduces the number of unnecessary echocardiograms.…”
Section: Discussionsupporting
confidence: 77%
“…Pulse oximetry has been assessed as a screening method for congenital heart defects in newborn babies in many studies. [18][19][20][21][22][23] Our study was also conducted to evaluate usefulness of pulse oximetry in screening CCHD in asymptomatic newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, using a threshold of < 95% in the foot only -the most frequently used test in previous studies 13,64,[67][68][69]71 -would have reduced the number of FPs by 84, but three critical cases (two Full cohort (n = 20,055, G in Figure 4) 0-6 hours (n = 4956, 25%) …”
Section: False-positivesmentioning
confidence: 86%
“…13 These findings have led to exploration of the possibility that pulse oximetry may be useful in detecting hypoxaemia associated with CHDs in apparently healthy newborns, and a number of studies have been published that have used pulse oximetry as a screen for CHDs in this group. 13,[62][63][64][65][66][67][68][69][70][71] In a systematic review published in 2007, we reviewed the eight published studies available at that time. 72 We highlighted a number of problems when assessing the accuracy of this test as there was a wide variation in methodology, particularly patient selection, timing of saturation measurement, cut-off levels for a positive test result, nature of CHD screened for, rigour of follow-up and type of oximeters used ( Table 2).…”
Section: Pulse Oximetrymentioning
confidence: 99%
See 1 more Smart Citation